Spatial epidemiology of Japanese encephalitis virus and other infections of the central nervous system infections in Lao PDR (2003-2011): A retrospective analysis - Rattanavong, S; Dubot-Pérès, A; Mayxay, M; Vongsouvath, M; Lee, SJ; Cappelle, J; Newton, PN; Parker, DM (Public Library of Science, 2020)
Background Central nervous system (CNS) infections are important contributors to morbidity and mortality and the causative agents for ~50% patients are never identified. The causative agents of some CNS infections have distinct spatial and temporal patterns.